The effects of sports participation on the development of left ventricular mass in adolescent boys. Issue 4 (7th March 2015) - Valente‐Dos‐Santos, João; Coelho‐E‐Silva, Manuel J.; Castanheira, Joaquim; Machado‐Rodrigues, Aristides M.; Cyrino, Edilson S.; Sherar, Lauren B.; Esliger, Dale W.; Elferink‐Gemser, Marije T.; Malina, Robert M.
<x xml:space="preserve">Abstract</x> Objectives To examine the contribution of body size, biological maturation, and nonelite sports participation to longitudinal changes of left ventricular mass (LVM) in healthy boys. Methods One hundred and ten boys (11.0–14.5 years at baseline) were assessed biannually for 2 years. Stature, body mass, and four skinfolds were measured. Lean body mass (LBM) was estimated. Biological maturation was assessed as years from age at peak height velocity (APHV). Sports participation was assessed by questionnaire. LVM was obtained from M‐mode echocardiograms using two‐dimensional images. To account for the repeated measures within individual nature of longitudinal data, multilevel random effects regression analyses were used in the analysis. Results LVM increased on average 42 ± 18 g from 11 to 15 years (P < 0.05) and 76 ± 14 g from 3.5 years pre‐APHV to 1.5 years post‐APHV (P < 0.05). The multilevel model with the best statistical fit (Model B) showed that changes of 1 cm in stature, 1 year post‐APHV, and 1 kg of LBM predicts 4.7, 0.5, and 1 g of LVM (P < 0.05), respectively. Conclusions Among healthy, male adolescents aged 11–15 years individual differences in growth and biological maturation influence growth of LVM. Subcutaneous adiposity and sports participation were not associated with greater LVM. Am. J. Hum. Biol. 27:530–537, 2015. © 2015 Wiley Periodicals, Inc.